2023
DOI: 10.1002/adfm.202214619
|View full text |Cite
|
Sign up to set email alerts
|

Sonodynamic Bacterial Inactivation Enhanced by an Actuator‐Integrated Mechanism

Abstract: Sonodynamic bacterial inactivation, a reactive oxygen species (ROS)empowered approach featuring high penetration depth and low health risk, is explored for antibiotic-free antibacterial treatment. However, the low yield and insufficient diffusion of ROS negatively affect the antibacterial efficacy of sonodynamic treatment, thus hindering its further development. Here an actuator-integrated mechanism is proposed for enhancing the sonodynamic efficacy of loaded sonosensitizers through motion-induced hydrodynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…The fluorescence imaging of infected mice indicated that the MAPC with pH-responsive Ce6-releasing properties showed an excellent antibacterial effect upon additional US treatment. Another study took the advantages of Au and organic sonosensitizers, Sun et al developed by Au nanorod coated thiol-poly (N, N-diethylacrylamide) for meso -tetrakis(4-sulfonatophenyl) porphyrin (TPPS@Au) loading [59] . TPPS@Au presented SDT antibacterial performance and performed multimodal motion via US propulsion.…”
Section: Nanoplatform For Delivery Of Organic Small-molecule Sonosens...mentioning
confidence: 99%
“…The fluorescence imaging of infected mice indicated that the MAPC with pH-responsive Ce6-releasing properties showed an excellent antibacterial effect upon additional US treatment. Another study took the advantages of Au and organic sonosensitizers, Sun et al developed by Au nanorod coated thiol-poly (N, N-diethylacrylamide) for meso -tetrakis(4-sulfonatophenyl) porphyrin (TPPS@Au) loading [59] . TPPS@Au presented SDT antibacterial performance and performed multimodal motion via US propulsion.…”
Section: Nanoplatform For Delivery Of Organic Small-molecule Sonosens...mentioning
confidence: 99%
“…As shown in Figure 9 a, Sun et al proposed the use of ultrasound-driven micro/nanomotors to enhance sono-dynamic antibacterial efficiency [ 116 ]. Specifically, they presented meso-tetra(4-sulfonatophenyl) porphyrin (TPPS)-modified gold nanorod (Au NR) motors as an illustrative example.…”
Section: Stimuli-responsive Antibacterial Nanomaterialsmentioning
confidence: 99%
“… ( a ) Schematic illustration of an ultrasound-propelled sonodynamic nanomotor for enhanced bacterial inactivation [ 116 ], Copyright 2023 Wiley-VCH. ( b ) Schematic illustration of Na + inserted metal–organic framework for rapid therapy of infected bacteria [ 114 ], Copyright 2021 Elsevier.…”
Section: Figurementioning
confidence: 99%
“…SDT has low invasiveness, high penetration depth, and can respond to US to produce ROS for sterilization, thereby avoiding the issue of antibiotic resistance. 11,12 SDT has shown great promise for treating infections and has gained increasing attention. [13][14][15] However, several issues still greatly limit the therapeutic efficacy of SDT for bacterial biofilms.…”
Section: Introductionmentioning
confidence: 99%